2007
DOI: 10.1126/science.1137999
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the Pairing Between let-7 and Hmga2 Enhances Oncogenic Transformation

Abstract: MicroRNAs (miRNAs) are ∼22-nucleotide RNAs that can pair to sites within messenger RNAs to specify posttranscriptional repression of these messages. Aberrant miRNA expression can contribute to tumorigenesis, but which of the many miRNA-target relationships are relevant to this process has been unclear. Here, we report that chromosomal translocations previously associated with human tumors disrupt repression of High Mobility Group A2 (Hmga2) by let-7 miRNA. This disrupted repression promotes anchorage-independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

58
860
1
14

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,070 publications
(933 citation statements)
references
References 26 publications
58
860
1
14
Order By: Relevance
“…In support of the significance of our findings, reduced expression of let-7 is correlated with poor prognosis, as lung cancer patients with the least let-7 expression had shorter time of survival after surgery (Takamizawa et al, 2004;Yanaihara et al, 2006). We and others subsequently showed that let-7 directly regulates multiple oncogenes, including RAS, MYC and HMGA2 (Johnson et al, 2005;Lee and Dutta, 2007;Mayr et al, 2007;Sampson et al, 2007), and promoters of cell-cycle progression, such as CDC25A, CDK6 and Cyclin D2 (Johnson et al, 2007). Moreover, administration of let-7 blocks the growth of cultured lung cancer cells (Johnson et al, 2007).…”
Section: Introductionsupporting
confidence: 82%
“…In support of the significance of our findings, reduced expression of let-7 is correlated with poor prognosis, as lung cancer patients with the least let-7 expression had shorter time of survival after surgery (Takamizawa et al, 2004;Yanaihara et al, 2006). We and others subsequently showed that let-7 directly regulates multiple oncogenes, including RAS, MYC and HMGA2 (Johnson et al, 2005;Lee and Dutta, 2007;Mayr et al, 2007;Sampson et al, 2007), and promoters of cell-cycle progression, such as CDC25A, CDK6 and Cyclin D2 (Johnson et al, 2007). Moreover, administration of let-7 blocks the growth of cultured lung cancer cells (Johnson et al, 2007).…”
Section: Introductionsupporting
confidence: 82%
“…This downregulation is due at least in part to impairment of the microprocessor function (Thomson et al, 2006). Among these downregulated micro-RNAs, several have been shown to be bona fide tumor suppressors (Calin et al, 2002;Mayr et al, 2007;Welch et al, 2007;Bonci et al, 2008;Cole et al, 2008;Esquela-Kerscher et al, 2008;Chen et al, 2009;Trang et al, 2010). On the other hand, certain micro-RNAs are overexpressed in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the fact that HMGA2 can be regulated by many microRNAs, such as the wellcharacterized ones in the let-7 family. 26,27 Nevertheless, we found HMGA2 overexpression is significantly associated with high-grade serous ovarian carcinoma 16 in this study (Table 4).…”
Section: Discussionmentioning
confidence: 45%